IMPLEMENTATION ANALYSIS OF SERVICE QUALITY IN BUSINESS PACKAGE DELIVERY SERVICES (Case PT. Indah Logistic cabang Pekanbaru) - Fitrianti Devi Rida; Lie Othman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
At this time the service is needed in services once by the community. For the provision of services in the field of services need to be improved so that the community as a customer service users were satisfied with the service provided. PT. Indah Logistic cabang Pekanbaru is engaged in the business of shipping services or goods.The research was conducted at PT. Indah Logistic cabang Pekanbaru. The problem formulation is How Quality Service at PT Indah Logistic cabang Pekanbaru? This study aims to determine the Quality of Service at PT. Indah Logistic cabang Pekanbaru and to determine the barriers faced by PT. Indah Logistic cabang Pekanbaru in Service Quality. In line with this research, the quality of service with a number of the respondents were 97 customers. This study uses quantitative analysis method using the theory put forward by some members about the quality of services. In this study researchers using indicators namely Utilization, Reliability, Responsiveness, Assurance, and Emphaty as a measure of the Quality of Service at PT. Indah Logistic cabang Pekanbaru. Technique used data collection with interviews and kuisioner ie, sampling techniques for Accidental Sampling. Shared data source that is divided into two primary data source is the source of information obtained through kuisioner, interviews with informants and secondary data obtained through the documents available in PT. Indah Logistic cabang Pekanbaru. From the research results obtained can be seen that the Quality of Service of PT. Indah Logistic cabang Pekanbaru categorized good arm.Keywords : Quality of Service, Tangible, Reliability, Responsiveness,Assurances and Emphaty